Anomalous single production of fourth generation t′ quarks at ILC and CLIC - A., Senol; A. T., Tasci; F., Ustabas (Elsevier BV, 2011)
We present a detailed study of the anomalous single fourth generation $t'$ quark production within the dominant Standard Model(SM) decay modes at future $e^+e^-$ colliders. We calculate the signal and background cross sections in the mass range 300-800 GeV. We also discuss the limits of $t'q$ and $t'qZ$ ($q=u,c$) anomalous couplings as well as values of attainable integrated luminosity for 3$$ observation limit.

12 pages, 14 figures, version to be published on Nucl.Phys. B
Keywords: High Energy Physics - Phenomenology; High Energy Physics - Phenomenology (hep-ph); Unified quantum theories; FOS: Physical sciences; Quantum scattering theory; Strong interaction, including quantum chromodynamics